Does Kafa'ah Apply To The Descendants Of The Prophet Muhammad. Examine The Concept Of Kafaah Towards The Alawites In Martapura, Banjar - Nadiyah Nadiyah; Norlaila Norlaila; Anwar Hafidzi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2021)
Abstract: This study emerged when there were problems among Habib and Syarifah in re -interpreting the concept of kafa'ah in marriage for the Alawiyin in the city of Martapura, South Kalimantan. This study is different from other researchers because the problem of endogamy is seen from sekufu or not in the sociological approach of society. The method used in this study is an empirical study with a sociological legal approach to the Alawiyin community who will hold a marriage. The finding of the research is that Kafa'ah in the alawiyin approach is as blood and as a descendant of the Prophet. If no similarity is found, then a discussion approach will be conducted on the agreement of all relatives to determine whether kafa'ah or not for the prospective companion later. Abstrak: Penelitian ini muncul Ketika ada permasalahan di kalangan Habib dan Syarifah dalam memaknai ulang konsep kafa’ah dalam pernikahan bagi kaum Alawiyin di Kota Martapura, Kalimantan Selatan. Penelitian ini berbeda dengan peneliti lainnya karena permasalahan endogami dilihat dari sekufu atau tidaknya dalam pendekatan sosiologi masyarakat. Metode  yang digunakan dalam penelitian ini adalah kajian empiris dengan pendekatan sosiologi hukum terhadap masyarakat alawiyin yang akan melangsungkan pernikahan. Temuan penelitian adalah bahwa Kafa’ah dalam pendekatan alawiyin adalah sedarah dan senasab dzuriyat Rasulullah. Jika tidak ditemukan yang senasab, maka akan dilakukan pendekatan diskusi terhadap kesepakatan semua kerabat untuk menentukan apakah kafa’ah atau tidak bagi calon pendampingnya nanti.